Hyperoxemia post thoracic surgery - Does it matter - Brat, Kristian; Chovanec, Zdenek; Mitas, Ladislav; Sramek, Vladimir; Olson, Lyle J; Cundrle, Ivan (Heliyon, 2023)
INTRODUCTION: Post-operative oxygen therapy is used to prevent hypoxemia and surgical site infection. However, with improvements of anesthesia techniques, post-operative hypoxemia incidence is declining and the benefits of oxygen on surgical site infection have been questioned. Moreover, hyperoxemia might have adverse effects on the pulmonary and cardiovascular systems. We hypothesized hyperoxemia post thoracic surgery is associated with post-operative pulmonary and cardiovascular complications. METHODS: Consecutive lung resection patients were included in this post-hoc analysis. Post-operative pulmonary and cardiovascular complications were prospectively assessed during the first 30 post-operative days, or hospital stay. Arterial blood gases were analyzed at 1, 6 and 12 h after surgery. Hyperoxemia was defined as arterial partial pressure of oxygen (PaO2)>100 mmHg. Patients with hyperoxemia duration in at least two adjacent time points were considered as hyperoxemic. Student t-test, Mann-Whitney U test and two-tailed Fisher exact test were used for group comparison. P values < 0.05 were considered statistically significant. RESULTS: Three hundred sixty-three consecutive patients were included in this post-hoc analysis. Two hundred five patients (57%), were considered hyperoxemic and included in the hyperoxemia group. Patients in the hyperoxemia group had significantly higher PaO2 at 1, 6 and 12 h after surgery (p < 0.05). Otherwise, there was no significant difference in age, sex, comorbidities, pulmonary function tests parameters, lung surgery procedure, incidence of post-operative pulmonary and cardiovascular complications, intensive care unit and hospital length of stay and 30-day mortality. CONCLUSION: Hyperoxemia after lung resection surgery is common and not associated with post-operative complications or 30-day mortality.